EVALUATING THE ROLE OF INTERNAL AUDIT AND ITS RELATION TO THE QUALITY OF FINANCIAL STATEMENT - Merawati, Luh Komang; Kumalasari, Putu Diah (Accounting Department,, 2020)
Purpose — This research aimed to obtain empirical evidence about the effect of accounting understandability, human resource competency and the role of internal audit as moderating variable on the quality of financial statement.Design/methodology/approach — This research was conducted on all financial administration officials and treasurers of local government in Bangli Regency with the primary data was obtained from questionnaires which were distributed to respondents. Sample was determined through purposive sampling. The analysis technique used was the multiple linear regression analysis.Findings — The results suggested that accounting understandability and the human resouce competency had positive effect on the quality of financial statement. Meanwhile, the relation between accounting understandibility and the quality of financial statement, the role of internal audit was not the moderating variable. Whereas, the effect of the role of internal audit was proven to moderate the relation between human resource competency and the quality of financial statement, with negative direction.Practical Implications — The financial statement of local government is a form of accountability on the use of local finances as the implementation of regional autonomy and the operational of local government to provide useful information in decision making.Originality/value — The quality of the said financial statement is determined by qualitative characteristics which are relevant, reliable, comparable and understandable, based on PP No. 71 of 2010.Keywords Accounting Understandability, Human Resource Competency, Role of Internal Audit, Quality of Financial StatementPaper Type Research Paper